A Clinical Odyssey: a case report on the diagnostic complexity and neurological management of Behçet's disease - Romano, Thaís Malta; Leandro, Sandra Isamar da Silva; Nardin, Karoliny de Lima; Zamoner, Beatriz Mazzer; Gervásio, Bruna Capello; Cavalcante, Fernanda Susy Bessa Menezes; Alves, Kelvin Corrêa Miranda; Matoso, Lavínnya Yáskara de Aquino; Oliveira, Francisco Ícaro Silvério de; Müller, Paulo Guilherme; Rivelli, Álvaro Moreira; Lima, Marina Carvalho de Souza; et al. (Brazilian Journal of Case Reports, 2023)
Behcet's Syndrome (BS) is a pathological condition that encompasses a diverse spectrum of clinical manifestations of a polysystemic nature. It is a chronically progressive inflammatory vasculitis, characterized mainly by recurrent episodes of oral and genital aphthous ulcers, ocular involvement, and other clinical expressions, including skin lesions and gastrointestinal disorders. The aim of this study is to present an atypical case of BS, as well as its correlation with the medical literature, to elucidate particularities of relevant significance for medical practice.